The Hidden Nature of Death and Grief - Shelagh McConnell (University of Calgary, 2012)
Western culture can be described as death-denying and youth-obsessed. Yet this has not always been the case. Only a few generations ago, death was very much part of life where people died at home with their families members caring for them. A shift occurred, in part, because of the unprecedented advances in medical science that the western world has seen over the past 40 years. Health care professionals now have the knowledge and the technology to prolong life in ways that were previously not only unattainable, but inconceivable. Regardless, the reality that death will eventually come for each of us has not changed; merely our perception of it has. This perception is influenced by the hidden nature of death in our society. This begs the questions: if death in our culture is something to hide, to conceal, and to keep secret, then what does that say about our ability to express grief? What does this mean for those who face it as part of their chosen profession? How might we understand the nature of suffering for those who turn toward the suffering of others? This paper interpretively examines the nature of hidden death and hidden grief in our society.